Four C-geranyl flavonoids from the flowers of Paulownia fortunei and their anti-inflammatory activity. Issue 22 (16th November 2020) - Zhang, Jing-Ke; Li, Meng; Li, Miao; Du, Kun; Lv, Jinjin; Zhang, Zhi-Guang; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: Four new C -geranyl flavonoids, paulownione D-G (1 –4 ) were isolated from the 50% acetone-H2 O extract of the flowers of Paulownia fortunei. The structures of the compounds were determined by extensive spectroscopic analyses (UV, IR, HR-ESI-MS, 1D and 2D NMR). All of the compounds (1 –4 ) exhibited potent protection effects in H9c2 cardiocytes against the lipopolysaccharide (LPS)-induced inflammation. Graphical abstract: